The Baikal subtype of tick-borne encephalitis virus is evident of recombination between Siberian and Far-Eastern subtypes. - Grigorii A Sukhorukov; Alexey I Paramonov; Oksana V Lisak; Irina V Kozlova; Georgii A Bazykin; Alexey D Neverov; Lyudmila S Karan (Public Library of Science (PLoS), 2023)
Tick-borne encephalitis virus (TBEV) is a flavivirus which causes an acute or sometimes chronic infection that frequently has severe neurological consequences, and is a major public health threat in Eurasia. TBEV is genetically classified into three distinct subtypes; however, at least one group of isolates, the Baikal subtype, also referred to as "886-84-like", challenges this classification. Baikal TBEV is a persistent group which has been repeatedly isolated from ticks and small mammals in the Buryat Republic, Irkutsk and Trans-Baikal regions of Russia for several decades. One case of meningoencephalitis with a lethal outcome caused by this subtype has been described in Mongolia in 2010. While recombination is frequent in Flaviviridae, its role in the evolution of TBEV has not been established. Here, we isolate and sequence four novel Baikal TBEV samples obtained in Eastern Siberia. Using a set of methods for inference of recombination events, including a newly developed phylogenetic method allowing for formal statistical testing for such events in the past, we find robust support for a difference in phylogenetic histories between genomic regions, indicating recombination at origin of the Baikal TBEV. This finding extends our understanding of the role of recombination in the evolution of this human pathogen.